Biometry of Adrenal Glands of Mixed-Breed Dogs - Trivilin, Leonardo Oliveira; Pessoa Júnior, Francisco de Assis; da Silva, Maria Aparecida; Milholli, Leandro André; Pastor, Felipe Martins; Bindaco, Adriano Lima Stelzer; Martins Filho, Sebastião; Nunes, Louisiane de Carvalho (Acta Scientiae Veterinariae, 2020)
Background: Differences of the size of the adrenal glands, in healthy dogs or in endocrinopathies, undermine correct diagnosis of endocrine disorders and evaluations of the adrenal cortex in relation to its size and possible correlation with endocrinopathies are rare. The aim of the present study was to perform measurements of the length, width, thickness and weight of the adrenal glands of young, adult and elderly mixed-breed dogs and correlate them with the age, sex and weight of animals. In addition, the areas occupied by the zona glomerulosa, zona fasciculata, and zona reticularis of the adrenal cortex were measured in order to establish a microscopic biometric pattern. Material, Methods & Results: The right and left adrenal glands of 12 young (six females and six males), 12 adults (six females and six males), and 12 elderly (six females and six males), all mongrels, derived from routine and necropsied in the Animal Pathology Sector of the Veterinary Hospital of the Federal University of Espírito Santo (HOVET-UFES) were weighed and the length, width, and thickness were measured. For the microscopic measurement of the adrenal cortex, 10 randomly selected samples were submitted to routine histological processing and the microscope slides were observed under a light microscope at 5× and 10× objectives, photodocumented and measurements were obtained from a random portion of the adrenal cortex and the zones composing the cortex were measured in triplicate with the aid of the computerized image analysis software. The left adrenal showed a greater average length than the right adrenal in young, adult, and elderly dogs. The size of the glands in the young and adult dogs is not influenced by the sex of the animals, but in older dogs the females had a greater mean width than the males. The weight of the animals presented a positive correlation in relation to the length and weight of the right and left adrenal glands in all studied groups. The age did not influence the length and weight variables of the glands. However, some differences in thickness and width were observed in the elderly group compared to those in other groups. For the microscopic measurements in the right adrenal gland, the cortex was 1.53 mm, being 0.21 mm for the glomerular zone (14.6% of the total adrenal cortex), 1.04 mm for the zona fasciculata (66.9%), and 0.29 mm for the zona reticularis (18.5%). In the left adrenal gland, the cortex was 1.83 mm, being 0.23 mm for the glomerular zone (13.2% of the total adrenal cortex), 1.23 mm for the zona fasciculata (63.96%), and 0.37 for the zona reticularis (22.84%). Discussion: Studies on the size of the adrenal gland in dogs using macroscopic biometrics are scarce, and the current study presents results regarding mixed-breed (male and female) dogs of different ages, which presented variation in size and weight, which could also influence the size of the adrenal gland. Thus, it can be observed that a variation of measurements can be found, especially for dogs with no defined breed. These results demonstrate the importance of studies that perform the macroscopic analysis of such glands. It was concluded that there was a clear variation in the size of the adrenal glands in mixed-breed dogs of different ages and both sexes; the left adrenal showed greater lengths and weights than the right gland. The sex of the animals did not influence the size of the glands in young and adult dogs, but in elderly dogs, the females showed a greater mean width than the males. The right and left adrenal cortices are formed at a greater percentage by the zona fasciculata, followed by the zona reticularis and zona glomerulosa.